Domination of volumetric toughening by silver nanoparticles over interfacial strengthening of carbon nanotubes in bactericidal hydroxyapatite biocomposite - Herkendell, Katharina; Shukla, Vishnu Raj; Patel, Anup Kumar; Balani, Kantesh (Materials Science and Engineering C, 2014)
In order to address the problem of bacterial infections in bone-substitution surgery, it is essential that bone replacement biomaterials are equipped with bactericidal components. This research aims to optimize the content of silver (Ag), a well-known antibacterial metal, in a multiwalled carbon nanotube (CNT) reinforced hydroxyapatite (HA) composite, to yield a bioceramic which can be used as an antibacterial and tough surface of bone replacement prosthesis. The bactericidal properties evaluated using Escherichia coli and Staphylococcus epidermidis indicate that CNT reinforcement supports growth of Gram negative E. coli bacteria ( 8.5% more adhesion than pure HA); but showed a strong decrease of Gram positive S. epidermidis bacteria ( diminished to 66%) compared to that of pure HA. Small amounts of silver (2-5 wt.%) already show a severe bactericidal effect when compared to that of HA-CNT (by 30% and 60% respectively). MTT assay confirmed enhanced biocompatibility of L929 cells on HA-4 wt.% CNT ( 121%), HA-4 wt.% CNT-1 wt.% Ag ( 124%) sample and HA-4 wt.% CNT-2 wt.% Ag ( 100%) when compared to that of pure HA. The samples with higher silver content showed decreased biocompatibility (77% for HA-4 wt.% CNT-5 wt.% Ag sample and 73% for HA-4 wt.% CNT-10 wt.% Ag). Though reinforcement of 4 wt.% CNT has shown an increase of fracture toughness by 62%, silver reinforcement has shown enhancement of up to 244% (i.e. 3.43 times). Accordingly, isolation of toughening contribution indicates that volumetric toughening by silver dominates over interfacial strengthening contributed by CNTs towards enhanced fracture toughness of potential HA-Ag-CNT biocomposites. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2021-03-08
Keywords: Antibacterial; Carbon nanotubes (CNTs); Cytocompatibility; Fracture toughness; Hydroxyapatite (HA); Silver (Ag)